Analisis Rencana Tarif Jalan Tol Berdasarkan Pendekatan Ability To Pay (ATP) Dan Willingness To Pay (WTP) Pada Rencana Ruas Jalan Tol Sigli - Banda Aceh - Faisal Syahrul; M. Isya; Fitrika Mita Suryani (Journal of The Civil Engineering Student, 2021)
Abstract The construction of toll roads is one of the government's efforts in facilitating the community to be able to carry out their mobility both in economic and social terms well and quickly. The construction of toll roads is also expected to be able to pass traffic with a safer, more comfortable and smoother level of service. Therefore, the government and related parties plan to build toll road in Aceh. It has 4 (four) roads with a total length of 455 km consisting of the 110 km of Binjai - Langsa toll road, 135 km of Langsa - Lhokseumawe toll road, 135 km of Lhokseumawe - Sigli toll road, and 75 km of Sigli - Banda Aceh toll road. The construction of the first toll road in Aceh will be started on the Sigli - Banda Aceh road corridor, and the construction or placement of the first stone will be started from Banda Aceh. The toll road construction has become the first toll road in Aceh. Consequently, the government has not yet set an official tariff. The purpose of this study is to determine and obtain effective rates based on analysis of the Ability to Pay (ATP) and Willingness to Pay (WTP) toll road tariffs. This research consists of data collection, namely primary and secondary data. Primary data are obtained based on direct observations in the field whereas for secondary data obtained from the relevant agencies. The data that has been obtained is then continued to the tariff analysis stage by using the ATP and WTP formulas. From the results of this analysis it can be concluded that the recommended tariff for the Sigli - Banda Aceh Toll Road is based on the average value of Ability To Pay (ATP) and Willingness To Pay (WTP) for class I (LV) vehicles of Rp. 56,000, - for class IIA (MHV) vehicles in the amount of Rp. 152,000, - for class IIB (LT LB) vehicles amounting to Rp. 118,500. Keywords: Toll Road, ATP, WTP, Toll Rates. Abstrak Pembangunan jalan tol merupakan salah satu usaha pemerintah dalam memudahkan masyarakat untuk bisa melakukan mobilitas mereka baik dalam hal ekonomi  maupun sosial dengan baik dan cepat. Pembangunan jalan tol juga diharapkan dapat melewatkan trafik dengan tingkat pelayanan yang lebih aman, nyaman, dan lancar. Pemerintah dan pihak terkait berencana untuk membangun ruas jalan tol Aceh, untuk ruas jalan tol itu sendiri memiliki 4 (empat) ruas jalan dengan panjang total 455 km yang terdiri dari ruas jalan tol Binjai - Langsa 110 km, ruas jalan tol Langsa - Lhokseumawe 135 km, ruas jalan tol Lhokseumawe - Sigli 135 km, ruas jalan tol Sigli - Banda Aceh 75 km. Sedangkan untuk pembangunan jalan tol pertama di Aceh ini dimulai pada koridor ruas jalan Sigli - Banda Aceh, dan untuk pengerjaan atau perletakan batu pertamanya dimulai dari Banda Aceh. Pembangunan jalan tol tersebut menjadi  jalan  tol pertama di Aceh, dan Pemerintah belum menetapkan tarif yang resmi. Tujuan penelitian ini untuk mengetahui dan mendapatkan tarifnefektif berdasarkan analisis Ability To Pay (ATP) dan Willingness To Pay (WTP) tarif jalan tol. Penelitian ini terdiri dari pengumpulan data yaitu data primer dan data sekunder. Data primer diperoleh berdasarkan pengamatan langsung di lapangan. Sedangkan untuk data sekunder diperoleh dari instansi terkait. Data yang telah diperoleh kemudian dilanjutkan ke tahap analisis tarif dengan cara menggunakan rumus ATP dan WTP. Dari hasil analisis tersebut dapat disimpulkan bahwa tarif yang direkomendasikan untuk Jalan Tol Sigli - Banda Aceh berdasarkan nilai rata- rata Ability To Pay (ATP) dan Willingness To Pay (WTP) untuk kendaraan golongan I (LV) sebesar Rp 56.000,-, untuk kendaraan golongan IIA (MHV) sebesar Rp 152.000,-, untuk kendaraan golongan IIB (LT LB) sebesar Rp 118.500,-. Kata kunci : Jalan Tol , ATP, WTP, Tarif Tol.